CALCULATION METHODS OF FLUID TRANSPORT IN GROUND CHANNELS - Bozorov , B.E.; Khakimov , K.Z. (Educational Research in Universal Sciences, 2023)
Currently, there are many studies conducted in our republic on the deformations of underground irrigation canals, but they cannot fully cover all the factors that affect the deformation of the irrigation canals. The task of developing the methods of calculation of non-washing velocities and liquid transport in open soil channels is revealed.